Chinese Philanthropy in Southeast Asia: Between Continuity and Change - MENKHOFF, Thomas (Institutional Knowledge at Singapore Management University, 2009)
What makes ethnic Chinese philanthropy tick? Thomas Menkhoff looks at what drives prominent Chinese business leaders to give back to society and offers a glimpse of the changing face of ethnic philanthropy.